2019
DOI: 10.4315/0362-028x.jfp-18-514
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding Revealed Mislabeling and Potential Health Concerns with Roasted Fish Products Sold across China

Abstract: Roasted fish fillet is a popular snack food in the People's Republic of China, and the market appeal can be reflected by the high price, which exceeds 330 RMB/kg in some cases. However, the labeled fish common name generally cannot be connected with a particular species, and the processing treatments make it a challenging task to identify fish species based on morphological characteristics. This study used full DNA barcoding and mini-DNA barcoding for species identification of 202 specimens sorted from 64 roas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…More specifically, U. japonicas is a small‐sized fish with low commercial value, and the mislabelling as codfish could lead to illegal profit. While great health concern with several species of Lagocephalus has already been reported (Xiong et al , ), the circulation of Lagocephalus species is strictly controlled in China, which, however, could be avoided by mislabelling as codfish. Finally, R. ectenurus and L. litulon products sold as codfish also represent an improved access to the market, given the great popularity and preference towards codfish in China (Xiong et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, U. japonicas is a small‐sized fish with low commercial value, and the mislabelling as codfish could lead to illegal profit. While great health concern with several species of Lagocephalus has already been reported (Xiong et al , ), the circulation of Lagocephalus species is strictly controlled in China, which, however, could be avoided by mislabelling as codfish. Finally, R. ectenurus and L. litulon products sold as codfish also represent an improved access to the market, given the great popularity and preference towards codfish in China (Xiong et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…The barcodes are nally estimated by multiplying the calculated 2step velocity in eqn (7) above by the tag time delay as…”
Section: Tension Propagation (Tp) Theory Explains the Source Of Discrepancy And Provides Solutionmentioning
confidence: 99%
“…Though researchers relied on DNA sequencing techniques for the identification of unknown species for a long time, in 2003, Hebert et al 2 proposed the mitochondrial gene (COI) region barcoding to classify cryptic species 3 from the entire animal population. Since then, several studies have shown the potential applications of barcoding in conserving biodiversity, 4 estimating phyletic diversity, identifying disease vectors, 5 authenticating herbal products, 6 unambiguously labeling the food products, 7,8 and protecting endangered species. 4 Traditional sequencing methods based on chemical analysis are still been widely used in the biological community to determine the barcodes.…”
Section: Introductionmentioning
confidence: 99%
“…Authentic samples of eight Gadiformes species and seventeen non-Gadiformes species commonly found on the market were used for specificity evaluation of the newly established triplex HRM assay in the present study, summarised in Table 1. All of them were obtained either form our previous studies (Xiong et al, 2020a(Xiong et al, , 2018(Xiong et al, , 2019, from the official food control authorities, or from the local supermarkets and morphologically identified by professionals. Moreover, DNA barcoding method (Handy et al, 2011) (data not shown) was used to cross-confirm the identity of all fish samples and the obtained sequences have been submitted to Genbank database (Table 1).…”
Section: Samples Collection and Dna Extractionmentioning
confidence: 99%